Analisis Strategi Bersaing Perusahaan Bus Menggunakan Teknik Rantai Markov, Game Theory, dan Short Route Models - Ade Momon Subagyo; Okky Jayadi; Ajeng Chintawati Dewi (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
Terminal Klari that located in Kabupaten Karawang has a function as a temporary stop place for public vehicles to raise and lower passengers. PO Bus with Klari – Purwokerto route is the object of the research. The large number of PO busses on this route causes loyalty of the passenger is decline. These observations were made on 6 PO Busses with Klari – Purwokerto route and with 6 attributes, there are price, service, facilities, ease of getting information, easy of getting tickets, and the travel time. The objective of the research is to determine the competitive strategies based on the analysis of the bus brand switching by bus passengers with Klari – Purwokerto route. This research utilizes a Markov chain, game theory, and short route models. The results of processing and analysis using Markov chain, obtained that the market share reached steady state in the 11th period with a yield of 16.09% for Dedy Jaya, 29.35% for Murni Jaya, 25.13% for Sinar Jaya, 7.97% for Pahala Kencana, 10.69% for DMI, and 10.77% for Dieng Indah. From game theory method the results of the game there are several alternative strategies for DMI Buses, such as improving the means of promotion and communication so the passengers can get information with easily about Bus DMI. The alternative route from the short route model is Klari Terminal - Tol Kranci / Pejagan - Bumi Ayu - Purwokerto, with a total distance of 304.7 km.